Analisis Keterampilan Berpikir Kritis Siswa tentang Pencemaran Lingkungan - Insar Damopolii; Jeni Jeni; Jan H. Nunaki; Lissa Imbiri; Nur Indah Ririn Fitriani Nasir (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
The problem of environmental pollution must be well thought out using critical thinking. Many young people gain knowledge about the problem of environmental pollution through learning activities at school. This research aims to analyze the students' critical thinking skills regarding environmental pollution. A total of 266 respondents have filled out the critical thinking test. The respondents are junior high school students in West Papua. There are twenty-one tests with two levels of multiple-choice answers. Tests are given online and as paper tests. Data obtained from respondents was calculated using percentages. The results showed that the student's critical thinking skills on environmental pollution problems in contrasting and comparing were moderate, identifying cause and effect was weak, and sequencing was moderate. Overall, the student's critical thinking skills regarding environmental pollution reached a weak category. The results of this study show that students' ability to think critically about environmental pollution is weak and needs to be improved. Future research can improve these skills so that the problem of pollution in the environment can be solved.